Pengaruh Motivasi Terhadap Komitmen Pegawai pada UPT. Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) Kecamatan Sanggar Kabupaten - Isratul Aini; Jaenab; Amirulmukminin (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The purpose of this research is to determine the influence of motivation on employee commitment at Upt. National Population and Family Planning Agency (BKKBN) Sanggar District, Bima Regency. So as to provide thoughts to the head of the National Population and Family Planning Agency (BKKBN) Sanggar District, Bima Regency. The method used in this research is a quantitative method, which is of the associative type. with a population of all employees at the National Population and Family Planning Agency (BKKBN) Sanggar District, Bima Regency, namely 34 people, consisting of 6 ASN employees, 4 contract employees, 24 honorary employees. The sample used in this research was a saturated sampling technique, namely the entire population was used as a sample at the UPT of the National Population and Family Planning Agency (BKKBN) Sanggar District, Bima Regency with a total of 34 employees. With data collection techniques by means of observation, questionnaires and literature study. This research determines statistical feasibility using validity tests, reliability tests, simple linear regression tests, correlation coefficient analysis (R), determination coefficient analysis (R2), and partial tests (t). The statistical results of the t test in the motivation variable obtained a calculated value of 7.605 with a t table value of 2.032 (7.605> 2.032) with a significant value of 0.000 which is smaller than the value of 0.05 (0.000 < 0.05), so H0 is rejected and Ha is accepted which is stated that "There is a significant influence of motivation on employee commitment at the UPT Service. National Population and Family Planning Agency (BKKBN) Sanggar District, Bima Regency.